2017
DOI: 10.1021/acs.jpca.7b07996
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boron Clusters on the Ignition Reaction of HNO3 and Dicynanamide-Based Ionic Liquids

Abstract: Many ionic liquids containing the dicynamide anion (DCA, formula N(CN)) exhibit hypergolic ignition when exposed to the common oxidizer nitric acid. However, the ignition delay is often about 10 times longer than the desired 5 ms for rocket applications, so that improvements are desired. Experiments in the past decade have suggested both a mechanism for the early reaction steps and also that additives such as decaborane can reduce the ignition delay. The mechanisms for reactions of nitric acid with both DCA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Because experiments have indicated that the reaction takes place primarily on the anion, most previous theoretical studies of the hypergolic reaction have focused on the reaction between the DCA – anion and HNO 3 . , In 2008, Chambreau and co-workers proposed a generalized mechanism for the reaction of DCA – + HNO 3 that was intended to imply fully solvated DCA – . The mechanism begins with the protonation of DCA – at the terminal N atom , to form HDCA, followed by NO 3 – attack of the electrophilic C atom.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because experiments have indicated that the reaction takes place primarily on the anion, most previous theoretical studies of the hypergolic reaction have focused on the reaction between the DCA – anion and HNO 3 . , In 2008, Chambreau and co-workers proposed a generalized mechanism for the reaction of DCA – + HNO 3 that was intended to imply fully solvated DCA – . The mechanism begins with the protonation of DCA – at the terminal N atom , to form HDCA, followed by NO 3 – attack of the electrophilic C atom.…”
Section: Introductionmentioning
confidence: 99%
“…More recent computational studies have begun to look outside of the fundamental DCA – + HNO 3 reaction. Reactions of HNO 3 with the intermediate HDCA have been calculated, , as it is formed during the initial step in the hypergolic reaction sequence, and proton transfer from HNO 3 to DCA – is favored at equilibrium in the condensed phase . Chambreau and co-workers showed that in the condensed phase, the reaction of HDCA + HNO 3 is calculated to have lower free energy barriers, but also substantially less free energy release, than the bare DCA – + HNO 3 reaction .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterizing the energetics of complex, rapid reactions takes a combination of experimental and computational efforts. In the present work, this approach is used to study a dicyanoborohydride-based EIL, selected due to its known hypergolicity and inclusion of boron. Energetic ionic liquids with the dicyanoborohydride anion have low ignition delays and high propellant performance characteristics, making these chemicals a desirable fuel for bipropellant systems. , By incorporation of boron into the chemical structure of a fuel, the energy density can be enhanced with an increase in the fuel’s volumetric enthalpy of combustion. , …”
Section: Introductionmentioning
confidence: 99%
“…Diffusion-limited reactivity of these ILs was addressed in work conducted by Chambreau et al in 2016 for gaseous HNO 3 reacting with aerosol droplets of IL, but the molecular dynamics (MD) simulations for liquid–liquid diffusion indicate that mixing of the two liquids, BMIM + DCA – and HNO 3 , is very rapid . Under 10 ms is considered a desirable ignition delay for aerospace applications. , Most of the ionic liquids examined to date have ignition delays that are longer, and considering fuel additives may be an option to reduce these ignition delays into a desirable range for in-space applications. …”
Section: Introductionmentioning
confidence: 99%